THE EFFECT OF GOOD CORPORATE GOVERNANCE AND FINANCIAL PERFORMANCE ON DISCLOSURE OF SUSTAINABILITY REPORT - Wijaya Triwacananingrum; Ellesia Briohny Gunawan; Shelly Lolitha; Velda Verika (Universitas Tidar, 2020)
This study aims to analyze the effect of Good Corporate Governance (GCG) which is proxied by independent commissioners, audit committees, managerial ownership, governance committees, and Financial Performance proxied by profitability, and leverage on disclosure of sustainability reports, using quantitative logistic regression methods and samples chosen using a purposive sampling method from annual report data and sustainability reporting published in 2018, published by the Indonesia Stock Exchange (IDX), obtained 249 research samples. The results of this study are the audit committee and the governance committee show a positive and significant effect on the sustainability report disclosure, while the independent board of commissioners, managerial ownership, profitability, and leverage do not show a significant effect on the sustainability report disclosure.